Theoretical prerequisites for the development of accounting in mining enterprises for the challenges of sustainable development - I.V. Zamula; О.V. Shavurska (Економіка, управління та адміністрування)
Factors affecting the state of enterprises in the mining industry of Ukraine were analyzed. It has been established that the mining industry has a significant potential for development, which is confirmed by significant reserves of natural resources. However, due to the extensive use of nature, there is depletion of the subsoil, which requires reforming the economic mechanism of their use. The mining industry is competitive at the international level, which is confirmed by the growth in the volume of exported products for 2017–2021. However, taking into account Ukraine’s integration aspirations for joining the EU, it is necessary to apply international norms and standards to increase the efficiency of enterprises in this field and reduce their negative impact on the environment. Solving the problems that occur in the mining industry of Ukraine requires a comprehensive approach and the implementation of environmentally safe technologies, eco-innovation. It is advisable to develop a strategy for the sustainable development of the mining industry based on the integration of three components: economic (competitiveness), environmental (resource efficiency, eco-safety) and social (employment and creation of safe working conditions). Effective management of natural resources is possible only if there is reliable and complete information about these natural resources. Accounting is an information system that provides internal users with information to make effective management decisions aimed at the exploitation and rational use of resources. The tools for implementing sustainable nature management are singled out: regulatory and legal, information and communication research and development. Taking into account the specifics of the mining industry, accounting objects were specified for further improvement of their organizational and methodological support.